Prevalence and associated factors to marijuana consumption in students between 18 to 25 years old from a Colombia’s public university - Martínez Torres, Javier; Arias Coronel, Florencio; Rodelo Vega, Abner Enrique; Jaraba Toro, Neydis Patricia; Meza Castellanos, Leyla Mariela; Contreras Jáuregui, Magda Milena; Padilla Sarmiento, Sandra; Villamizar Carrillo, Diana Janeth (Universidad y Salud, 2016)
Introduction: Drug use in general has spread around the world and, therefore, it is considered to be a serious public health problem that concerns health systems, since they are substances that produce addiction and entails cognitive impairment with greater emphasis on memory, learning and loss of internal control. Objective: To determine prevalence and associated factors to marijuana consumption during the last month and once in a lifetime in public university students in Colombia who are between 18 to 25 years old. Materials and methods: A descriptive cross sectional study was performed in 474 healthy subjects between 18 to 25 years old in Pamplona, Colombia. The associated factors to  marijuana consumption (gender, religious belief, academic semester, social status, age, smoking and alcohol consumption.), were collected by a structured survey. Prevalence for each factor was calculated and associated factors were established through the construction of regression models. Results: At the time of the survey, it was found that 7.1% of students smoked marijuana in the last month and 22% expressed having used it at least once. The regression models show that having the habit of smoking cigarette was associated to marijuana consumption (OR 23.33 CI95% 6.92-78.68). Conclusion: Marijuana use in the study population was high and factors such as the consumption of cigarettes are associated with that of marijuana. These data could be used to provide educational intervention programs.